Pulp synthesis using bamboo raw materials through unbleached and bleached processes - Siregar, Sri Hilma; Rahmadini, Syafri; Hasmalina, Nasution; Rizki, Ramadhanti Aulia; Eri , Kafri (The Indonesian Chemical Society, Chapter Nusa Tenggara and The University of Mataram, 2023)
This study aims to see the potential of bamboo as a new raw material for the Indonesian pulp industry, specifically for the manufacture of pulp products, because in Indonesia, the import value for dissolving is still high, and the raw materials used still use wood plants. This study consists of three stages: the pre-hydrolysis stage using water, the cooking stage with the kraft pulping method, and bleaching using the elemental chlorine-free (ECF) method. Bamboo flakes that run into the pre-hydrolysis process decreased the Kappa Number value of pulp produced, which ranges from 4.63% - 14.52% compared to bamboo flakes that do not run into the pre-hydrolysis process. The brightness increase to 0.844% - 2.96% compared to bamboo flakes that do not run into the process of pre-hydrolysis. For pulp products, the value of Alpha Cellulose obtained is around 89.18% - 90.32%.